Analisis Maraknya Warga Miskin yang Kecanduan Judi Online di Indonesia - Safira Mustaqilla; Siti Sarah; Eva Zahara Salsabila; Aina Fadhilla (Glossary : Jurnal Ekonomi Syariah, 2023)
Gambling is a criminal act by risking a certain amount of money where the party who wins will get all the betting money. Gambling can be detrimental to society and damage the nation's morals. Gambling behavior will become a problem when it starts to approach the diagnostic criteria for pathological gambling, where the behavior is mal-like. -adaptive and sustainable, giving rise to a series of further problems, such as continuing to try to bet even though you have lost many times. According to all religious views, gambling is something that is prohibited. Online gambling games played by people are the result of social interactions that occur between them. Social interaction can be likened to a currency that has two sides: positive and negative. One example of the negative impact is what happens to people who take part in online gambling games. As technology develops, gambling is now moving to a place that is a little more elite. Technological advances too. changing the way of playing gambling, along with developments in technology, now gambling has moved to a slightly more elite place. Advances in technology have also changed the way of playing gambling. Now, gambling doesn't have to be hidden like in the past, just by sitting relaxed in front of a computer or cellphone that is connected to the internet network, we can play this haram game.